Colonic perforation in 91- year- old man with severe Covid-19 infection - Khin Phyu Pyar; Min Aung Shan; Soe Win Hlaing; Diwon; Zarni Htet Aung; Soe Min Aung; Nyan Lin Maung; Aung Phyoe Kyaw (Journal of Clinical Microbiology and Biochemical Technology - Peertechz Publications, 2020)
A-91-year old man had severe Covid-19 infection (bilateral pneumonia, SaO2 85% on air). He was treated with antibiotics, oxygen, dexamethasone and convalescent plasma therapy. On day 28 symptom onset, he noticed abdominal distension without abdominal pain. CT abdomen revealed pneumoperitoneum. An area of perforation at colon with mucosal haemorrhage was seen in laparotomy. Right hemicolectomy was done. Histology showed mucosal oedema, infiltration with inflammatory cells mainly polymorphs and lymphocytes, congested vessels with areas of haemorrhage in the mucosa.